Self-Interaction Is Critical for Atg9 Transport and Function at the Phagophore Assembly Site during Autophagy - He, Congcong (The American Society for Cell Biology, 2008)
Autophagy is the degradation of a cell's own components within lysosomes (or the analogous yeast vacuole), and its malfunction contributes to a variety of human diseases. Atg9 is the sole integral membrane protein required in formation of the initial sequestering compartment, the phagophore, and is proposed to play a key role in membrane transport; the phagophore presumably expands by vesicular addition to form a complete autophagosome. It is not clear through what mechanism Atg9 functions at the phagophore assembly site (PAS). Here we report that Atg9 molecules self-associate independently of other known autophagy proteins in both nutrient-rich and starvation conditions. Mutational analyses reveal that self-interaction is critical for anterograde transport of Atg9 to the PAS. The ability of Atg9 to self-interact is required for both selective and nonselective autophagy at the step of phagophore expansion at the PAS. Our results support a model in which Atg9 multimerization facilitates membrane flow to the PAS for phagophore formation.